2012
DOI: 10.1371/journal.pone.0035163
|View full text |Cite
|
Sign up to set email alerts
|

NGF Causes TrkA to Specifically Attract Microtubules to Lipid Rafts

Abstract: Membrane protein sorting is mediated by interactions between proteins and lipids. One mechanism that contributes to sorting involves patches of lipids, termed lipid rafts, which are different from their surroundings in lipid and protein composition. Although the nerve growth factor (NGF) receptors, TrkA and p75NTR collaborate with each other at the plasma membrane to bind NGF, these two receptors are endocytosed separately and activate different cellular responses. We hypothesized that receptor localization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 82 publications
2
48
0
Order By: Relevance
“…TrkA and p75 NTR are membrane receptors for Nerve Growth Factor (NGF), which mediate antagonistic functions; TrkA mediate cell survival while p75 NTR usually induces programmed cell death. It has been shown that NGF enhances the interaction between TrkA and microtubules in lipid rafts, whereas p75 NTR is sorted out of the rafts (Pryor et al, 2012), suggesting that raft/ cytoskeleton interactions may be relevant for cell fate. Regarding adhesion, a mechanism involving cytoskeleton and raft endocytosis has been proposed, so that when cells detach from the matrix, rafts are internalized and targeted to recycling endosomes in an actin-and microtubule-dependent manner; on the contrary, upon a new adhesion event, lipid rafts return to the cell membrane, through microtubules (Balasubramanian et al, 2007).…”
Section: Communication With the Cytoskeletonmentioning
confidence: 99%
“…TrkA and p75 NTR are membrane receptors for Nerve Growth Factor (NGF), which mediate antagonistic functions; TrkA mediate cell survival while p75 NTR usually induces programmed cell death. It has been shown that NGF enhances the interaction between TrkA and microtubules in lipid rafts, whereas p75 NTR is sorted out of the rafts (Pryor et al, 2012), suggesting that raft/ cytoskeleton interactions may be relevant for cell fate. Regarding adhesion, a mechanism involving cytoskeleton and raft endocytosis has been proposed, so that when cells detach from the matrix, rafts are internalized and targeted to recycling endosomes in an actin-and microtubule-dependent manner; on the contrary, upon a new adhesion event, lipid rafts return to the cell membrane, through microtubules (Balasubramanian et al, 2007).…”
Section: Communication With the Cytoskeletonmentioning
confidence: 99%
“…Reprinted with permission from the Proceedings of the National Academy of Sciences (Steketee et al, 2011). Pryor, McCaffrey, Young, & Grimes, 2012). Finally, Trk activation is linked to three main intracellular signaling cascades via a wide variety of adaptor proteins, including mitogen-activated kinase (MAPK) (Howe et al, 2001), phospholipase C-gamma (PLCg) (Ming et al, 1999), and phosphoinositol-3-kinase (Quinn & Wadsworth, 2008), further emphasizing the possibility that each signaling endosome, with varying numbers of neurotrophin cargoes and receptors, likely has a distinct molecular and signaling profile.…”
Section: Sorting and Signalingmentioning
confidence: 99%
“…Studies suggest the endosomal lipid environment also regulates endosome signaling. Prior to endocytosis, Trk receptors are often found in sphingolipid-cholesterol lipid rafts (Kamiguchi, 2006;Simons & Gerl, 2010), and neurotrophin activation of Trk receptors may stimulate Trk receptors to move into lipid rafts (Pryor et al, 2012). Lipid rafts are dynamic microdomains in the plasma membrane (Dietrich, Yang, Fujiwara, Kusumi, & Jacobson, 2002;Kusumi, KoyamaHonda, & Suzuki, 2004) formed by the preferential association of cholesterol with saturated fatty acids and glycosphingolipids (Simons & Vaz, 2004).…”
Section: Lipids and Signalingmentioning
confidence: 99%
See 2 more Smart Citations